Remote Concurrent Engineering: A-Team Studies in the Virtual World - Burgin, Mariko S.; Hawkinson, Karla; Kataria, Tiffany; Matousek, Steven; Park, Katherine; Scott, Valerie; Shah, Rashmi; Tran, Austin; Wessen, Randii; Zusack, Steven (2021 IEEE Aerospace Conference (50100), 2021)
NASA Jet Propulsion Laboratory's (JPL's) Architecture Team (A-Team) has nearly a decade of experience in maturing early formulation mission and technology concepts by combining innovative collaborative engineering methods with cutting-edge subject matter expertise and advanced analysis tools in an in-person environment. When COVID-19 forced JPL's workforce to work remotely in March 2020, A-Team had to quickly pivot from an in-person collaborative environment to a remote working environment. Through introspection, careful planning, and considerable practice, A-Team was able to develop new operating procedures to effectively continue early formulation studies in a virtual environment. A-Team has held over 57 remote studies in the 10 months since the start of mandatory telework at JPL in March 2020. In the remote setting, A-Team conducts studies in half-day sessions with clients and subject matter experts (SMEs) via videoconferencing, shared computer screens, and digital collaborative tools. The key lesson is that increased staffing and planning is needed to prepare and successfully run remote A-Team studies. Remote A-Team studies require careful selection of the appropriate tools for security, accessibility, and usability within the NASA/JPL environment. Knowledge capture methods and templates need to be thought out and agreed upon in advance as there is less room for improvising in a remote format. Various communication channels have to be monitored to allow for team coordination while maintaining fruitful participant engagement during a session. In addition, technical backup for all roles within the A-Team have to be identified to allow the study to continue even if a team member's connectivity is temporarily interrupted. Finally, careful thought has to be put into methods and processes to create a collaborative environment in a virtual space such that a group of experts who are only connected via the internet can experience the creative spark and flow of a great collaborative and innovative study.